2010
DOI: 10.2174/1876823701002020012
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Cancer Risk: The Evidence for Causal Association~!2009-04-22~!2009-06-16~!2010-07-13~!

Abstract: Increased body mass index (BMI), as an approximation of body adiposity, is a risk factor for developing several adult malignancies. To quantify these risks, we reported a comprehensive systematic review (Lancet 2008; 371: 569-78) of prospective observational studies determining associations between BMI and risk of incident cancer for 20 cancer types. We demonstrated that associations are: (i) sex-specific; (ii) exist for a wider range of malignancies than previously thought; and (iii) are broadly consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…A meta-analysis prospective study of 282 000 cancer cases from population of 4·8 million patients demonstrated similarly consistent findings across disease sites and sexes ( 8 ) . Applying the Bradford-Hill hypotheses of strength, consistency, specificity, temporality, biological gradient, plausibility, coherence, experimental evidence and analogy, obesity is a strong candidate to be a causal factor in the development of cancer as detailed in a review by Renehan et al ( 15 , 16 ) .…”
Section: Epidemiologymentioning
confidence: 99%
“…A meta-analysis prospective study of 282 000 cancer cases from population of 4·8 million patients demonstrated similarly consistent findings across disease sites and sexes ( 8 ) . Applying the Bradford-Hill hypotheses of strength, consistency, specificity, temporality, biological gradient, plausibility, coherence, experimental evidence and analogy, obesity is a strong candidate to be a causal factor in the development of cancer as detailed in a review by Renehan et al ( 15 , 16 ) .…”
Section: Epidemiologymentioning
confidence: 99%